Anti-inflammatory properties of polysaccharides from edible fungi on health-promotion: a review - Yin, Zhenhua; Zhang, Juanjuan; Qin, Jingjing; Guo, Lin; Guo, Qingfeng; Kang, Wenyi; Ma, Changyang; Chen, Lin (Frontiers in Pharmacology, 2024)
Edible fungus polysaccharides have garnered significant attention from scholars due to their safety and potential anti-inflammatory activity. However, comprehensive summaries of their anti-inflammatory properties are still rare. This paper provides a detailed overview of the anti-inflammatory effects and mechanisms of these polysaccharides, as well as their impact on inflammation-related diseases. Additionally, the relationship between their structure and anti-inflammatory activity is discussed. It is believed that this review will greatly enhance the understanding of the application of edible fungus polysaccharides in anti-inflammatory treatments, thereby significantly promoting the development and utilization of edible fungi.